IDENTIFIKASI PENYEBAB TIMBULNYA LIMBAH PROYEK KONSTRUKSI DI KOTA AMBON - Evana Bintang, Syakira; Taihuttu, Felix; Sangadji, Fauzan A. (Jurnal Teknik Sipil dan Arsitektur, 2026)
Construction waste is a common issue faced in development projects, primarily due to inefficient material usage, technical errors, and lack of supervision. In Ambon City, the increase in construction activities has not always been accompanied by proper waste management. This study aims to identify the most dominant types of construction waste and analyze the main factors causing the generation of such waste from the perspective of stakeholders, namely contractors, consultants, and government agencies. The method used is a descriptive quantitative approach through a two-stage questionnaire distribution. The first stage was conducted to determine the most dominant type of waste, while the second stage measured the intensity of the factors causing waste generation based on project phases: planning, procurement, and implementation. A total of 77 respondents were involved in this study. Data analysis techniques included validity tests, reliability tests, as well as mean analysis and ranking using the SPSS program. The results show that ceramic tiles are the most dominant type of waste. The main contributing factor is the large number of unusable ceramic tile cuts due to mismatched room dimensions, followed by incomplete working drawings and careless material handling. Waste management strategies derived from respondent feedback have been validated by experts and deemed feasible for on-site implementation.